1999
DOI: 10.1161/01.cir.99.25.3260
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α–Converting Enzyme and Tumor Necrosis Factor-α in Human Dilated Cardiomyopathy

Abstract: This study has shown that increased myocardial TACE expression is associated with elevated myocardial TNF-alpha expression in both mRNA and protein levels in clinically advanced DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 24 publications
2
67
3
Order By: Relevance
“…8,27,28 Our previous studies have demonstrated that TNF-a cascade is activated in human DCM via expression of its converting enzyme and iNOS and that this activation may be related to the clinical severity of DCM. 5,6,29 Although this study could not confirm a direct causal relationship between activation of the TLR4-signaling pathway and LV dysfunction induced by inflammatory mediators, the LPS-challenged mouse model has demonstrated that TLR4 is tightly linked with NF-kB activation and expression of proinflammatory cytokines such as interleukin 1 and TNF-a in the heart. 30 These inflammatory mediators have been shown in various reports to produce LV dysfunction.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…8,27,28 Our previous studies have demonstrated that TNF-a cascade is activated in human DCM via expression of its converting enzyme and iNOS and that this activation may be related to the clinical severity of DCM. 5,6,29 Although this study could not confirm a direct causal relationship between activation of the TLR4-signaling pathway and LV dysfunction induced by inflammatory mediators, the LPS-challenged mouse model has demonstrated that TLR4 is tightly linked with NF-kB activation and expression of proinflammatory cytokines such as interleukin 1 and TNF-a in the heart. 30 These inflammatory mediators have been shown in various reports to produce LV dysfunction.…”
Section: Discussioncontrasting
confidence: 60%
“…30 These inflammatory mediators have been shown in various reports to produce LV dysfunction. 5,6,29,31,32 Nemoto et al 33 have recently reported that LPS challenge resulted in depression of LV systolic function in wild-type mice, whereas no significant changes in LV systolic function were noted in TLR4-deficient mice. The activated TLR4-signaling pathway in the heart may therefore be linked to inflammatory mediators (eg proinflammatory cytokines and iNOS) and to cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of TNF␣-converting enzyme (TACE), which cleaves TNF and its receptors from the cell surface, has been demonstrated in human atherosclerotic plaques (44). TACE levels have also been shown to correlate with the degree of left ventricular systolic dysfunction in patients with dilated cardiomyopathy (45), and it has been suggested that circulating levels of sTNFRII may be a surrogate marker for worsening left ventricular function and/or remodeling (18).…”
Section: Mattey Et Almentioning
confidence: 99%
“…Shedding of TNF-␣ is mediated predominantly by TACE (ADAM17), 24 and TACE activity is strongly associated with ventricular dilatation and cardiac dysfunction in human heart failure. 11 TNF-␣ receptor II, p75, can be released in soluble form by TACE or on binding to TNF-␣. 25 Compared with TNF-␣, soluble p75 level has a longer half-life and is easily detectable and thus a preferred measure of overall TACE bioactivity.…”
Section: Fedak Et Al Timp-3 Deficiency and Cardiomyopathy 2405mentioning
confidence: 99%